Remote health service vulnerabilities and responses to the COVID‐19 pandemic. (20th November 2020) - Fitts, Michelle S.; Russell, Deborah; Mathew, Supriya; Liddle, Zania; Mulholland, Edward; Comerford, Clarissa; Wakerman, John
Abstract: The rapid response to the COVID‐19 pandemic in Australia has highlighted the vulnerabilities of remote Aboriginal and Torres Strait Islander communities in terms of the high prevalence of complex chronic disease and socio‐economic factors such as limited housing availability and overcrowding. The response has also illustrated the capability of Aboriginal and Torres Strait Islander leaders and the Aboriginal Community Controlled Health Services Sector, working with the government, to rapidly and effectively mitigate the threat of transmission into these vulnerable remote communities. The pandemic has exposed persistent workforce challenges faced by primary health care services in remote Australia. Specifically, remote health services have a heavy reliance on short‐term or fly‐in, fly‐out/drive‐in, drive‐out staff, particularly remote area nurses. The easing of travel restrictions across the country brings the increased risk of transmission into remote areas and underscores the need to adequately plan and fund remote primary health care services and ensure the availability of an adequate, appropriately trained local workforce in all remote communities.